The Role of Muslim Psychologists in the New Paradigm of Human Development: 5-7 April 1995 15-7 Dhl al Qa‘dah 1415 Lahore, Pakistan (American Journal of Islam and Society, 1996)
The Islamization of Knowledge movement is gaining steady momentumamong Muslim scholars. Efforts are being made to examine differentacademic disciplines from an Islamic perspective, which is a clear indicationof the growing desire to develop a new hework of knowledge. Oneresult of this is the above-mentioned conference, which was organized bythe Society for the Advancement of Muslim Psychology (SAMP), Pakistan,with the collaboration of the International Institute of Islamic Thought(IIIT), Pakistan.SAMP was founded by Syed Azhar Ali Rizvi, chairman of theDepartment of Psychology, Government College, Lahore, some ten yearsago. Among the society’s objectives are:to promote the cause of Muslim psychology as a basic as well asan applied science, and of Muslim psychologists as academiciansand professionals working for the welfare of the individual and thesociety; to explore ways and means of improving the quality oftraining, research, and professional competence of Muslim psychologists;and to apply the teachings of the Qur’an and hadith andthe interpretations of eminent Muslims thinkers in the diagnosis,treatment, and rehabilitation of those who need psychological care ...